Characteristics of Color Development in Seeds of Brown- and Yellow-Seeded Heading Chinese Cabbage and Molecular Analysis of Brsc, the Candidate Gene Controlling Seed Coat Color - Ren, Yanjing; He, Qiong; Ma, Xiaomin; Zhang, Lugang (Frontiers in Plant Science, 2017)
The proanthocyanidin (PA) is the main flavonoids which affect the seed coat color in Brassica species. In this paper, the accumulation of flavonoids was analyzed in the seeds of brown-seeded (B147) and yellow-seeded (B80) heading Chinese cabbage (Brassica rapa L. ssp. Pekinensis). It is found that the content of phenolic compounds in B147 were significantly more than that of B80 by using dimethylaminocinnamaldehyde (DMACA) staining and toluidine blue O staining. In previous studies, the locus associated with seed coat color has been mapped. The results of whole genome re-sequencing showed that there are large fragment deletions variation in the mapping region between the brown-seeded parent ‘92S105’ and the yellow-seeded parent ‘91-125’. Based on the B. rapa genome annotation information, the TRANSPARENT TESTA GLABRA 1 (TTG1), is likely to be the candidate gene controlling seed coat color. A 94-base deletion was found in the 96th bases downstream of the initiation codon in the TTG1 of yellow seed, thus, the termination codon TGA was occured in the 297th base which makes the full length of TTG1 of yellow seed is 300 bp. Based on the differential sequences of TTG1 of brown and yellow seed, a functional marker, Brcs-yettg1, was developed to detect the variation of TTG1. Quantitative real-time PCR analysis of BrTTG1 in different tissues showed that expression levels of BrTTG1 was not tissue-specific. During the whole seed development period, the expression of BrTTG1 in B147 was higher than that of B80. The expression levels of four structural genes, BrDFR, BrANS, BrANR1 and BrANR2 in B147 were also higher than those in B80. The co-segregation molecular markers obtained in this report and TTG1 related information provide a basis for further understanding of the molecular mechanism of seed coat color in heading Chinese cabbage.